2021
DOI: 10.1029/2020jb020577
|View full text |Cite
|
Sign up to set email alerts
|

A Geology and Geodesy Based Model of Dynamic Earthquake Rupture on the Rodgers Creek‐Hayward‐Calaveras Fault System, California

Abstract: The Hayward fault in California's San Francisco Bay area produces large earthquakes, with the last occurring in 1868. We examine how physics‐based dynamic rupture modeling can be used to numerically simulate large earthquakes on not only the Hayward fault, but also its connected companions to the north and south, the Rodgers Creek and Calaveras faults. Equipped with a wealth of images of this fault system, including those of its 3D geology and 3D geometry, in addition to inferences about its interseismic creep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 121 publications
(224 reference statements)
0
26
0
Order By: Relevance
“…Dynamic rupture modeling can greatly aid in determining likely multi-fault rupture scenarios given specific rock properties and 3D geometry (e.g., R. A. Harris et al, 2021). Incorporating step-over and branching connections into the integer-programming framework is described by Geist and Parsons (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic rupture modeling can greatly aid in determining likely multi-fault rupture scenarios given specific rock properties and 3D geometry (e.g., R. A. Harris et al, 2021). Incorporating step-over and branching connections into the integer-programming framework is described by Geist and Parsons (2020).…”
Section: Discussionmentioning
confidence: 99%
“…9.1 A 2D SEAS multi-fault scenario on a shallowly dipping normal fault with four curved splay faults SEAS simulations including more than one fault segment and complex fault geometries are methodologically challenging (Romanet et al 2018;Galvez et al 2020;Luo et al 2020;Barbot 2021) (see also Sec. 10.2), but crucial to understand large earthquakes that often span several segments of natural regional-scale fault networks (Plesch et al 2007;Ando & Kaneko 2018;Ulrich et al 2019;Harris et al 2021). The mechanics of splay fault systems are of specific interest to seismic and tsunami hazard assessment and to understand…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…See Figure 1 for locations of fault section boundaries and paleoseismic sites. Dynamic rupture simulations of large earthquakes on partially creeping strike-slip faults explore the influence that patches of aseismic creep have on earthquake behavior (Harris et al, 2021;Lozos et al, 2021) 2021) used estimates of the interseismic creep-rate pattern derived from geodetic and microseismicity data to inform initial stress conditions for dynamic rupture simulations (see Figure 7 in Harris et al, 2021). The southern portion of the Rodgers Creek fault from Santa Rosa to the bend in the fault at the intersection with the northern Hayward fault (Figure 1) is assumed to be predominantly locked (Jin & Funning, 2017).…”
Section: Multi-fault Rupturementioning
confidence: 99%
“…In the absence of creep-rate observations to the south of this bend, the creep-rate on the Hayward fault is tapered to ∼4 mm/yr near Point Pinole (Funning et al, 2007;Shakibay Senobari & Funning, 2019). In Harris et al (2021), areas of lower initial shear stress and, thereby, lower initial stress drop were defined by fault patches with interseismic creep rates ≥3 mm/yr and separately by patches with creep rates ≥1 mm/yr. Results of the Harris et al (2021) simulations showed that while rupture nucleating on both the Rodgers Creek and Hayward fault were capable of rupturing through San Pablo Bay in some instances, expanded areas of creep beneath San Pablo Bay and/or the inclusion of interfacial cohesion in the shallow subsurface (0-3 km depth) limited rupture propagation through the bay.…”
Section: Multi-fault Rupturementioning
confidence: 99%